An investigation into modes of technological disruption in South African businesses - Bassa, Nahim Yusuf (University of the Witwatersrand, Johannesburg, 2021)
The term and understanding of disruption remains an engaging and expansive space. Seminal works of literature ranging from Joseph Schumpeter to Clayton Christenson have introduced the concept of technology disruption and its subsequent effects. However, this research has predominately been focused on the pre-digital era. Technology advancements have created tectonic changes in the business world and resulted in a myriad of outcomes in what is being termed the 'era of digital.' To date, the literature on technological disruption in this digital era has been filled through thought-leadership and point-of-view pieces by leading consultancy and professional service organisations and revealed a gap in the theoretical applications of technological disruption in the business world. This study followed a constructivist paradigm and positioned whether technology disruption can be explained in terms of a market engagement, demand, and production disruption model. A purposive sampling method was executed using the researcher’s professional network across a set of 11 interviews. The sample represented an adequate number of male and female respondents, senior executives, mainly over the age of 40, from multiple South African industries, occupying various C-Suite roles. The results of the survey supported the model and the interlinkages between the different technology modes. These findings have implications on how technological change creates disruptive opportunities or threats for firms and how they can take advantage of it. Suggestions for future research are provided.
A research report submitted to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in the field of Digital Business), 2021
Keywords: Disruption; Modes; Technology; Technology disruption; SDG-8: Decent work and economic growth